Outcome Prediction of Treatment of Graves’ Hyperthyroidism with Antithyroid Drugs - Piantanida, E.; Lai, A.; Sassi, L.; Gallo, D.; Spreafico, E.; Tanda, M. L.; Bartalena, L. (Hormone and Metabolic Research, 2015)
Graves’ disease is the most common cause of hyperthyroidism in iodine-replete areas and is ultimately due to antibodies interacting with the TSH receptor on thyroid follicular cells [TSH-receptor antibody (TRAb)]. Antithyroid drugs (ATDs) belonging to the family of thionamides are the first-line treatment in Europe. ATD treatment is commonly continued for 18–24 months. Its major limitation is the high rate of relapses after drug withdrawal. Factors particularly bound to subsequent relapses are the large thyroid volume, smoking habit, persistence of TRAb in the circulation at the end of treatment, and the post-partum period. Under these conditions, consideration should be given to a definitive therapy for hyperthyroidism (radioiodine treatment, thyroidectomy), particularly if the patient is at risk of cardiovascular complications that might be exacerbated by persistence or recurrence of hyperthyroidism.
Keywords: Graves’ hyperthyroidism; Graves’ orbitopathy; thionamides; methimazole; TSH-receptor antibody; smoking; goiter